2000
DOI: 10.1128/iai.68.11.6384-6390.2000
|View full text |Cite
|
Sign up to set email alerts
|

Role of Streptolysin O in a Mouse Model of Invasive Group A Streptococcal Disease

Abstract: Many of the virulence factors that have been characterized for group A streptococci (GAS) are not expressed in all clinical isolates. One putative virulence factor that is present among most is streptolysin O (Slo), a protein with well-characterized cytolytic activity for many eukaryotic cells types. In other bacterial pathogens, proteins homologous to Slo have been shown to be essential for virulence, but the role of Slo in GAS had not been previously examined. To investigate the role of Slo in GAS virulence,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
81
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(85 citation statements)
references
References 40 publications
4
81
0
Order By: Relevance
“…The molecular events included phage-mediated virulence gene acquisition, single nucleotide variant accumulation, and horizontal transfer of the 36-kb region encoding the virulence factors Nga and Slo (61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73), likely mediated by generalized transduction (24). It is now clear from our analysis that a complex multistep (9).…”
Section: Concluding Commentmentioning
confidence: 86%
“…The molecular events included phage-mediated virulence gene acquisition, single nucleotide variant accumulation, and horizontal transfer of the 36-kb region encoding the virulence factors Nga and Slo (61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73), likely mediated by generalized transduction (24). It is now clear from our analysis that a complex multistep (9).…”
Section: Concluding Commentmentioning
confidence: 86%
“…SLO hemolytic assays were carried out essentially as described by Limbago et al (26). Briefly, an overnight culture of test strains was adjusted to an absorbance of 1.0 at 600 nm, after which the supernatant was separated by centrifugation for 10 min at 7,500 ϫ g and then filtered (pore size, 0.25 m).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, another GAS virulence factor, streptolysin O (SLO), which binds to cholesterol in red blood cell membranes, causing lysis, reportedly exerts various neurological effects, increases capillary permeability, and induces dermal necrosis in rabbits (1). On the other hand, direct studies of the role of SLO during infection recently revealed that the contribution of SLO to GAS virulence was limited in a murine dermonecrosis invasive infection model (26). Still another factor is streptolysin S (SLS), which like SLO is potently cytolytic (1).…”
mentioning
confidence: 99%
“…Hemolysins, or cytolysins, are well-recognized features of many bacterial species, including streptococci, and are generally associated with damage to the membranes of a variety of mammalian cell types. Examples of streptococcal cytolysins include streptolysin O (SLO) and streptolysin S (SLS) of group A streptococci (GAS), the beta-hemolysin/cytolysin of group B streptococci (GBS), and the pneumolysin of Streptococcus pneumoniae, each of which has been implicated as a virulence factor in animal models of infection (3,4,33,49). In this investigation, we describe a molecular approach used to identify the genetic locus responsible for cytolysin production in S. iniae.…”
mentioning
confidence: 99%